The Effect of Corporate Environmental Reporting and Malaysian Environmentally Sensitive Public Listed Companies on Organizational Behavior - Sarah Yuliarini; Eva Wany (Institut Bisnis dan Informatika Kesatuan, 2026)
In recent years, increasing global concern over climate change has encouraged firms to integrate sustainability principles into corporate practices and reporting frameworks. This study aims to examine the influence of Environmental, Social, and Governance (ESG) on organizational behavior with corporate environmental responsibility as a mediating variable, specifically within Malaysian publicly listed companies categorized as environmentally sensitive. A quantitative approach is employed using content analysis of annual reports, sustainability reports, and corporate websites over a seven-year period (2018–2024), with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that ESG does not have a significant direct effect on organizational behavior, and its indirect effect through corporate environmental responsibility is also not significant. However, corporate environmental responsibility has a significant positive influence on organizational behavior. This shows that internal environmental responsibility is the key factor in shaping organizational behavior, rather than ESG reporting alone. In conclusion, organizational behavior in environmentally sensitive firms is primarily driven by corporate environmental responsibility, while ESG functions more as a reporting and compliance mechanism rather than a direct driver of behavioral change.